TFEB Dependent Autophagy-Lysosomal Pathway: An Emerging Pharmacological Target in Sepsis - Liu, Xin; Zheng, Xinchuan; Lu, Yongling; Chen, Qian; Zheng, Jiang; Zhou, Hong (Frontiers in Pharmacology, 2021)
Sepsis is a life-threatening syndrome induced by aberrant host response towards infection. The autophagy-lysosomal pathway (ALP) plays a fundamental role in maintaining cellular homeostasis and conferring organ protection. However, this pathway is often impaired in sepsis, resulting in dysregulated host response and organ dysfunction. Transcription factor EB (TFEB) is a master modulator of the ALP. TFEB promotes both autophagy and lysosomal biogenesis via transcriptional regulation of target genes bearing the coordinated lysosomal expression and regulation (CLEAR) motif. Recently, increasing evidences have linked TFEB and the TFEB dependent ALP with pathogenetic mechanisms and therapeutic implications in sepsis. Therefore, this review describes the existed knowledge about the mechanisms of TFEB activation in regulating the ALP and the evidences of their protection against sepsis, such as immune modulation and organ protection. In addition, TFEB activators with diversified pharmacological targets are summarized, along with recent advances of their potential therapeutic applications in treating sepsis.